Role of Probiotics in Secondary Prophylaxis of Hepatic Encephalopathy - Hafiz Abdul Rehman, Tazeen Nazar, Bilal Aziz, Hussain Farooq, Numreen Nazar, Abdulraffay (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the role of probiotics in combination with standard therapy in secondary prophylaxis of hepatic encephalopathy. Methods: This Randomized Controlled Trial was carried out in the Medical Wards of King Edward Medical University/Mayo Hospital, Lahore from 15th October, 2018 to 14th January, 2020. 166 patients selected via simple random sampling technique were divided into two groups. Group A received Lactulose whereas Group B received Lactulose plus Probiotic. A three months follow up for each patient was done. Absence of hepatic encephalopathy at the end of treatment was considered Effective treatment response. Primary end point was completion of three months or development of hepatic encephalopathy. Patients’ responses were noted on a pre-designed proforma. Data analysis was done using SPSS version 23.0. Results: Out of a total of 166 patients comprising 83 males and 83 females, mean age of the patients was 54.11±7.76 years. A statistically significant difference was found between the study groups inserum ammonia levels(p-value=<0.001). At 3rd month follow up 79(47.59%) patients had no episode of hepatic encephalopathy as assessed on West Haven grading (grade 0) followed by hepatic encephalopathy noted in 56(33.73%) patients; 25(15.06%)ingrade 3, 22(13.25%)ingrade 4 and 9(5.42%)in grade 2 respectively. p-value between the study groups and end result of the patients demonstrated statistically significant difference(p-value=0.028) Practical Implication: Overt hepaticencephalopathy is a common and frequent complication in patients with decompensated chronic liver disease. Various treatment modalities have proven beneficial. In this study we have shown the adjuvant role of probiotics with the standard lactulose therapy in remission and secondary prophylaxis of overt hepatic encephalopathy. Conclusion: Probiotics in conjunction with conventional lactulose therapy is more effective than standard lactulose therapy alone in remission and maintenance of secondary prophylaxis of overt hepatic encephalopathy. Keywords: Hepatic Encephalopathy, Secondary prophylaxis, Standard therapy, Probiotic